En Bloc Resection of the Temporal Bone and Temporomandibular Joint for Advanced Temporal Bone Carcinoma. (23rd January 2015) - Kutz, Joe Walter; Mitchell, Derek; Isaacson, Brandon; Roland, Peter S.; Allen, Kyle P.; Sumer, Baran D.; Barnett, Sam; Truelson, John M.; Myers, Larry L.
Abstract : Advanced skin malignancies involving the temporal bone can involve the temporomandibular joint and glenoid fossa. Many of these tumors can be removed with a lateral temporal bone resection; however, extensive involvement of the glenoid fossa should include an en bloc resection of the temporal bone, glenoid fossa, and condyle. We describe a novel surgical approach that is an extension of a temporal bone resection that includes the glenoid fossa and condyle in an en bloc resection with the temporal bone. This procedure has been performed in 7 patients with advanced carcinoma of the temporal bone involving the glenoid fossa. There were no short‐term complications as a result of the surgical approach. The addition of a middle fossa craniotomy and inclusion of the glenoid fossa and condyle as part of an en bloc resection of the temporal bone can be performed safely.